THE INTERRELATIONSHIP BETWEEN RAPE AND CONSTRUCTIONS OF MASCULINITY AND DEVELOPMENT ASSISTANCE IN THE DEMOCRATIC REPUBLIC OF CONGO (DRC): Received: 29th April 2021; Revised: 28th July 2021, 7th August 2021, 18th October 2021; Accepted: 1st December 2021 - Gordon, Ruth Frimpomaa Anarfi (PEOPLE: International Journal of Social Sciences, 2021)
War is an event, at its occurrence destroys nations. More than five million lives were claimed during the conflict of the DRC. It caused heinous destruction to properties, infrastructure, impeded national growth, and caused a lot of citizens, especially women and girls to suffer greatly, in addition, stereotyping the nation as “the rape capital of the world”. It is against this background that this study sought to delve into the case of the DRC to explore why the DRC was tagged “the capital of rape in the world”. To find out why rape was used as a weapon of war against women and girls. To explore whether it was a way of money-making by the influence of external bodies or a belief. This study employed a qualitative approach relying on administered questionnaires, literature from publications, presented papers, journals, books, and useful websites. Pert the findings or results, rape cases in the DRC is not a belief, but rare cases and in a way, money-making on the part of some NGOs and indigenes. This paper concludes with some questions: Are neighbouring countries and international organizations still trooping in to exploit the natural resources of DRC? Is the DRC truly the “rape capital of the world”? Is this not a myth or probably a stereotype since some NGOs offer natives the platform to inflate the figures based on forging rape to get medical attention? This is a wake-up call for the African Union, the United Nations, Human Rights Watch etc. to take strict measures to curb the menace (violence against women and girls during conflicts or wars).